FORMULASI TEPUNG JAGUNG DAN IKAN LELE DUMBO (Clarias gariepinus) PADA PEMBUATAN NUGGET FORMULATION OF CORN FLOUR AND AFRICAN CATFISH (Clarias gariepinus) IN THE MAKING OF NUGGETS - Indah, Widoretno; Nawansih, Otik; Yuliana, Neti (Jurusan Teknologi Hasil Pertanian, 2023)
The study aimed to determine the effect of the formulation of corn meal and catfish on the sensory and chemical characteristics of fish nuggets and to obtain the best formulation of corn flour and catfish on fish nugget products. This study was arranged in a Completely Randomized Block Design with a single factor of six levels and four replications. The formulations of corn flour and catfish in the manufacture of fish nuggets were P0 (10 g and 190 g as controls), P1 (10 g and 190 g), P2 (20 g and 180 g), P3 (30 g and 170 g), P4 (40 g and 160 g), and P5 (50 g and 150 g). Sensory observations were carried out by scoring, hedonic, and chemical properties tests. The Bartlett test and the addition of the data by the Tuckey test tested the homogeneity of the data. The data were analyzed by variance to determine the effect between treatments. If there was a significant effect, the data was further analyzed with the Least Significant Difference (L.S.D.) test at a 5% level. The results showed that the formulation of corn flour and catfish significantly affected sensory properties (texture, taste, and overall acceptability) and chemical properties (ash, fibre, fat, protein, and carbohydrate content) but not significantly on colour parameters alongside the scent and moisture content of the nuggets. The formulation of corn flour and catfish that produced the best fish nuggets was the P3 treatment (30 g corn flour and 170 g catfish) on cooked nuggets having a texture score of 7.62 (slightly dense and somewhat compact, taste score 7.08 (typical of fish), score colour 6.64 (yellow-brown) aroma score 6.88 (less typical of fish) and overall acceptance of 7.27 (like), and the best half-cooked nugget chemical properties resulted in water content of 74.70%, ash content of 1.27%, 8.61% protein content, 2.08% fat content, 1.22% crude fibre content and 12.09% carbohydrate content.